Penerapan Tema Rancangan Modern Tropis pada Fasilitas Pusat Fotografi Digital di Denpasar: Bahasa Indonesia - Agung Lanang Pradnyana; I Wayan Wirya Sastrawan; Agus Kurniawan (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2023)
Photography is one of the professional jobs that can be achieved through photography training and competency tests and can become a commercial area for everyone, especially in big cities like Denpasar. The development of the interest of the Balinese people, especially Denpasar in the field of photography can be seen from the existence of a community of the Perhimpunan Fotografer Bali (PFB) and ISI Denpasar which has a photography study program located in Denpasar City. Judging from these conditions, a forum or place is needed for photography enthusiasts to carry out training to obtain professional certification. Through data collection methods, both literature studies, interviews with managers and observations, then data analysis was carried out, it was found that photography enthusiasts needed facilities to support photography activities, especially training places and competency tests. These supporting facilities are in the form of theory classrooms, computer rooms, indoor and outdoor photography studio rooms, photography galleries and camera retail. So, the results of this study are designing a photography center facility in Denpasar with the application of a tropical modern design theme.